The future of nutrition : an insider's look at the science, why we keep getting it wrong, and how to start getting it right - Campbell, T. Colin, 1934-; Disla, Nelson (BenBella Books, Inc., 2020)
Campbell takes on the institution of nutrition itself: the history of how we got locked in to focusing on "disease care" over health care; the widespread impact of our reverence of animal protein on our interpretation of scientific evidence; the way even well-meaning organizations can limit what science is and is not taken seriously; and what we can do to ensure the future of nutrition is different than its past.